Integrating English with total physical response for pre-schoolers’ cognitive development - Govindan Nair, Krishnavani Anmal; Nachiappan, Suppiah; Teck, Wong Kung (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2017)
This study explores the integration of English with Total Physical Response (TPR) for pre-schoolers’ cognitive development. Research was built upon, review of cognitive developmental theorists, stakeholders, teachers’ feedback and experience. Five TPR related lesson plans are specially created and vetted by experts in order to collect data related to young learners’ cognitive development with the integration of English with TPR. This study employs a naturalistic observational methodology. The researchers conducted observation, attentive listening and tool field notes concurrently. A structured reflective note from the researchers is also used for analyses. The observation procedure seeks to record descriptive details about cognitive processes, ambience, and social activities among preschoolers. The findings indicate that there is improvement in language progressions, observable cognitive output with the ability to think, questioning skill, justifying thoughts and opinions and higher interest in learning through TPR. Therefore it is concluded that by integrating English with TPR, pre-school educators can maximize the output of their teaching.